IMPLEMENTASI PERSETUJUAN TINDAKAN KEDOKTERAN (INFORMED CONSENT) DALAM PERJANJIAN TERAPEUTIK OLEH TENAGA KESEHATAN TERHADAP PASIEN RUMAH SAKIT DI PROVINSI BALI - Ida Ayu Sri Kusuma Wardhani (University of Udayana, 2014)
Health is the most important part of human life that can affect productivity and optimal human activity. When a person's health is compromised, then that person will seek treatment in health care facilities in the hospital one of them in order to get action. Measures of medicine containing the high risk should get written consent from patient/family called Informed Consent. The legal relationship between health professionals with patients occurs because of the agreement that causes the therapeutic relationship inspaningverbintenis law (treaty effort). Similarly in the Bali Provincial Hospital in any medical act especially those containing a high risk, which is done by some health professionals are also using the Informed Consent. But if there is negligence actions that cause harm, who will be responsible for the risks in the suffering patient / family? and how the efforts of patient / family to resolve medical disputes against the risk of Informed Consent? The method used in this research is an empirical law derived from primary data and secondary data. The nature of the study is descriptive, with qualitative data analysis. Overall the results of these analyzes are presented in the description which describes the complete problem under study, along with a critical discussion. Based on the Theory of Legal System of L. M. Friedman, legal systems theory described by Soerjono Soekanto be legal efficacy theory, the theory of Hans Kelsen responsibility, and legislation as well as the results of research in the field, it is known that the liability of health professionals based on Informed Consent Agreement Therapeutic Hospital in Bali province is on the doctor who signed the operator of the informed consent form. However, if the patient / family prosecute acts of negligence committed by health professionals, the hospital will be responsible jointly and severally against such negligence. From the result of research in the hospital in the province of Bali, demands action against medical negligence are usually resolved by kinship means or mediation